A systematic review on the effectiveness of enteral immunonutrition (EIN) on pre- and post-operative outcomes in gastric cancer patients - Ruth Merry Paranjothi Yanok; Iklil Iman Mohd Sa'id; Chau, Shin Hwa; Seng, Kai Yee; Nik Shanita Safii; Yap, Wei Boon (Penerbit Universiti Kebangsaan Malaysia, 2020)
Gastric cancer is one of the most common upper gastrointestinal malignancies. To date, enteral immunonutrition (EIN) has gained increasing attention as it is found to effectively enhance the host’s immunity and improve the metabolic status of gastric cancer patients undergoing gastrectomy. The health-boosting effects of EIN are believed to originate from a number of nutritional elements such as omega-3 fatty acids, glutamine, arginine and nucleic acid precursors that help reduce the incidences of post-operative complications and shorten the length of hospital stay among the aforementioned patients. However, little was known about the consistency of health-boosting benefits conferred by EIN. Hence, according to PRISMA (Preferred Reporting Items for Systematic reviews and Meta-Analyses) protocol, this systematic review was carried out using nine meticulously and specifically selected full-length articles focusing on the pre- and post-operative effects of EIN including physical, biochemical, clinical and immunological outcomes on gastric cancer patients. Among the selected articles, seven of them focused on post-operative EIN while the remaining two concentrated on pre-operative EIN. In most of the selected studies, more than one immunonutritional components (arginine, glutamine, omega-3 fatty acid, RNA) were integrated. Patients receiving EIN showed significantly improved immunity, for example, increase in CD4+ T and NK cell counts that are responsible for fighting pathogens. In addition to that, individuals receiving EIN also showed increased levels of inflammatory biomarkers in their sera such as pre-albumin and transferrin. This results in shorter period of post-operative hospital stay that in turn permits progressive healing process and increases the survival rate due to minimal frequency of post-operative infections. Conclusively, our systematic review acknowledges that regardless of the initiation timing (pre-operative or post-operative) of immunonutrition, EIN can improve the overall health status of gastric cancer patients including infection complications and the length of hospital stay through regulation of immune responses.